Factors associated with nursing students' online learning self-efficacy: A descriptive cross-sectional study - Demirelli, Elmas Gül; Karaçay, Pelin (Nurse education today, 2024)
When compared to face-to-face education, nursing students in online education should be highly motivated and self-disciplined. Therefore, revealing the factors associated with the online learning self-efficacy of nursing students is fundamental. This descriptive cross-sectional study examined nursing students' online learning self-efficacy levels and associated factors. This study was conducted with a total of 632 undergraduate nursing students and took place between February and April of the 2020–2021 academic year in Turkey. A questionnaire including sociodemographic characteristics, features of online learning, and the “Online Learning Self-Efficacy Scale” was used to collect data. Data were analyzed using descriptive statistical methods, t-tests in independent groups to test for differences between groups, Pearson Correlation, One-Way Variance (ANOVA), Tukey, and multiple linear regression analysis. The mean score of nursing students in the Online Learning Self-Efficacy Scale was 74.54 ± 14.42 (min-max: 22–105). Factors associated with the online self-efficacy level of nursing students were: being female, using computers/tablets or more than one technological device in online education, the belief that online education offers the advantage of more study time, the belief that online education prevents time lost by commuting, frequency of attending online courses, satisfaction level with online education, and technology usage skill level. These factors explained 55 % of variance. Some factors related to students studying in different disciplines affect students' self-efficacy in online education. Nursing students' online learning self-efficacy skills can be enhanced by creating positive learning online environments and offering support in the use of online technologies.